Text Research of the Book Persian Language-Correspondence and Business Documents (Based on Persian and Russian languages) - Maryam Shafaghi; Asghar Ghodrati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Administrative correspondence is one of the standard Persian languages that has its own writing characteristics in terms of vocabulary, fixed structural and style stereotypes. Teaching such a style of language use, especially teaching language as a foreign language (based on the example of teaching Persian to Russian speakers in the subject of research) has its own characteristics and methodological solutions. Reading and translating the text of Persian administrative correspondence has difficulties for Russian speakers because of the following reasons: first, the tendency towards Arabicism in correspondence, second, the change of the meaning of some Arabic words adopted in Persian, and third, the characteristic of flattery extremism as an expression of politeness in Persian correspondence. All these reasons have made it more difficult for foreigners to read and understand the basic text of administrative and commercial correspondence. Although the book Persian Language - Correspondence and Business Documents written by Habib Najafov, is a valuable treasure of the collection of administrative and commercial correspondence between Iran and the Soviet Union/ Russian Federation, at the same time it has its drawbacks and the absence of a Persian-language editor in reviewing the texts of the "conversation" section, the use of incorrect stylistic applications in the language under the influence of frequent errors of Persian speakers, teaching the use of words in the language, which have become obsolete, such as "concerning the superiors" are some of them.